2003
DOI: 10.1063/1.1563730
|View full text |Cite
|
Sign up to set email alerts
|

Observation of optical phonon instability induced by drifting electrons in semiconductor nanostructures

Abstract: We have experimentally proven the Cerenkov generation of optical phonons by drifting electrons in a semiconductor. We observe an instability of the polar optical phonons in nanoscale semiconductors that occurs when electrons are accelerated to very high velocities by intense electric fields. The instability is observed when the electron drift velocity is larger than the phase velocity of optical phonons and rather resembles a ''sonic boom'' for optical phonons. The effect is demonstrated in p-in semiconductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The gain increases faster with higher n e , as can be seen in Fig. 3, where peak phonon gain is plotted as a function of v d for four different n e for an assumed T e of 1030 K. Electrically driven phonon gain was previously predicted in GaAs-based QW's, [23][24][25] but in GaN, electronphonon coupling M 2 is almost an order of magnitude higher and the phonon lifetime is longer, hence the chances of observing stimulated LO emission are greatly enhanced.…”
supporting
confidence: 53%
“…The gain increases faster with higher n e , as can be seen in Fig. 3, where peak phonon gain is plotted as a function of v d for four different n e for an assumed T e of 1030 K. Electrically driven phonon gain was previously predicted in GaAs-based QW's, [23][24][25] but in GaN, electronphonon coupling M 2 is almost an order of magnitude higher and the phonon lifetime is longer, hence the chances of observing stimulated LO emission are greatly enhanced.…”
supporting
confidence: 53%
“…This so-called 'Cerenkov acousto-electric effect' was predicted [1,2] and observed [3][4][5][6] in the 1960s in semiconductors with large piezoelectricity [3] such as CdS, and multivalley crystals with electron-phonon interaction via the deformation potential [5]. A similar effect, optical phonon instability, was also predicted [6][7][8][9][10] in the 1960s, and recently by Komirenko et al [11], and has been recently demonstrated by Liang et al [12] in a GaAs-based semiconductor nanostructure. It is well known that optical phonons play a major role in the energy relaxation of fast (hot) electrons in semiconductors [13].…”
Section: Introductionmentioning
confidence: 64%
“…1,2 Therefore, it is always an important subject to understand the carrier-phonon interaction occurring in the heterointerfaces of semiconductor nanostructures. [3][4][5] Recently, the development of femtosecond laser sources has made it possible to perform coherent phonon spectroscopy in various condensed matters with optical pump-probe techniques. [6][7][8][9] The carrier and phonon dynamics, particularly the transient carrier-phonon interaction, can now be studied at the femtosecond timescale.…”
Section: Bias-dependent Carrier and Phonon Dynamics In Semiconductor-mentioning
confidence: 99%